Epidermolytic Hyperkeratosis in a Resource-Limited Setting: A Case Report from Yemen - Alshami M.A; Mohana M.J; Alshami A.M (Achievements and Challenges of Medicine and Medical Science Vol. 10, 2025)
Epidermolytic hyperkeratosis is a rare autosomal dominant disorder of cornification with a prevalence of 1:100,000 to 1:300,000, which affects both sexes equally. It presents at birth with generalized erythema, blisters, and erosions. In the months after birth, erythema and blistering decrease, while hyperkeratotic scaling that is especially prominent over the joints, neck, and dorsum of hands and feet increases. Neonates with EHK are at risk of developing severe infections, electrolyte imbalance, and sepsis, due to disruption of the epithelial barrier. This study reports the case of a 10-year-old girl who presented to the dermatology clinic with dirty brown, corrugated hyperkeratotic plaques involving joint flexures and the trunk. She had similar lesions arranged in a cobblestone pattern over the knees, elbows, and dorsal hands and feet, in addition to multiple superficial erosions. She had a history of generalized erythroderma and trauma-related blistering at the time of birth. All other family members were healthy and had no such skin manifestations. The patient was treated with 40% urea cream, which she used as tolerated. Management for EHK is primarily targeted at symptom control and relief. Improved neonatal care has decreased morbidity secondary to sepsis, dehydration, and electrolyte imbalances. Further research into improved diagnostic and therapeutic strategies will ensure better management of this condition, ultimately improving the quality of life for affected individuals.